Bermain Ice Breaking dalam Bahasa Arab untuk Anak Usia Dini - Lubis, Hilda Zahra; Sejati, Indah Sri; Fadillah, Ranti; Safira, Lailan; Aminah, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Arabic vocabulary mastery (mufrodat) is one of the main keys to mastering Arabic. However, a monotonous learning environment often becomes an obstacle for students to achieve this mastery. This study aims to analyze the effectiveness of icebreaker strategies in increasing student engagement in learning Arabic mufrodat. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The results of the study showed that icebreaker strategies were able to change the classroom atmosphere from initially boring to more active, fun, and conducive. This strategy succeeded in attracting students' attention and increasing their participation in the learning process. In conclusion, icebreakers are an effective tool for creating an entertaining learning environment while supporting the improvement of Arabic vocabulary mastery. This strategy can be adapted as an innovative learning method to create a more interactive and motivating atmosphere for students